2021
DOI: 10.1093/humupd/dmab028
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin-1 in the female reproductive system and pregnancy

Abstract: BACKGROUND Stanniocalcin-1 (STC-1) is a widely expressed glycoprotein hormone involved in a diverse spectrum of physiological and pathophysiological processes including angiogenesis, mineral homeostasis, cell proliferation, inflammation and apoptosis. Over the last 20 years, numerous studies have reported STC-1 expression within female reproductive tissues including the uterus, ovaries and placenta and implicated STC-1 in processes such as ovarian follicular development, blastocyst implantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 143 publications
(305 reference statements)
0
16
0
Order By: Relevance
“…PCOS patients’ impaired endometrial receptivity and reproductive outcomes may be affected by changes in numerous signal pathways as the disease progresses ( 17 , 42 , 43 ). In our study, the DEPs were shown to be involved in ferroptosis and mitochondrial dysfunction based on the KEGG pathway and subcellular location prediction system.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS patients’ impaired endometrial receptivity and reproductive outcomes may be affected by changes in numerous signal pathways as the disease progresses ( 17 , 42 , 43 ). In our study, the DEPs were shown to be involved in ferroptosis and mitochondrial dysfunction based on the KEGG pathway and subcellular location prediction system.…”
Section: Discussionmentioning
confidence: 99%
“…Stanniocalcin 1 (STC1) is a glycoprotein assigned to the ‘regulation of cell migration’ category (GO:0030334), that reduces calcium levels and increases phosphate levels in the cells and tissues. STC1 is involved in many processes, including angiogenesis, mineral homeostasis, cell proliferation, inflammation, and apoptosis [ 37 , 38 ]. In our experiment, CHEM increased the level of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription level of CLDN4 is significantly higher in the endometrium of idiopathic infertility and minimal endometriosis, indicating that CLDN4 overexpression might be negatively linked to endometrial receptivity ( 25 ). STC1 serves in many processes ( 26 ), and it correlates with receptivity markers during the window of implantation ( 27 ). In patients with endometriosis, STC1 is upregulated in the mid-secretary eutopic endometrium ( 28 ).…”
Section: Discussionmentioning
confidence: 99%